Synthesis of Some Novel Non-Nucleoside Reverse Transcriptase Inhibitor - Bapna, Mayank; Nema, R.K. (Asian Journal of Chemistry, 2010)
New approaches towards synthesis of new anti-HIV agents have lead to development of non-nucleoside reverse transcriptase inhibitors (NNRTI's). New NNRTI's have been synthesized by substitution of 2-amino diaryl pyridine. In the present study a series of substituted 2-amino pyrimidine derivatives were synthesized using Schotten-Bauman and Baker-Venkatraman rearrangement principle. The formed derivatives were characterized by spectral analysis and the purity was checked by TLC.